Consumer preferences and perceptions on dealcoholised wine. - Chan, Sook Mun; Mohd Adzahan, Noranizan; Abdul Karim, Muhammad Shahrim; Karim, Roselina; Olusegun, Lasekan; Regenstein, Joe M. (Taylor & Francis, 2012)
The article analyses Malaysian consumer attitudes toward dealcoholised wine and whether its religious regulation status affects a consumer's perception of the product. A closed-end questionnaire was used to ascertain the consumer's knowledge and awareness, attitudes, potential behaviours and general opinions about dealcoholised wine. Two hundred respondents were interviewed and results showed that 20% of the respondents knew about dealcoholised wine but only 9% consumed it. Most respondents (81%) perceived dealcoholised wine as not halal, hence the low consumption level. Despite a strong belief that dealcoholised wine has health benefits, consumers' culture of mild to no alcohol drinking contributed to its low preference.